Fabrication, characterization and modelling of triple hierarchic PET/CB/TPU composite fibres for strain sensing - Qin, Yijing; Qu, Muchao; Pan, Yamin; Zhang, Chunhua; Schubert, Dirk W. (Composites Part A-Applied Science and Manufacturing, 2020)
In this study, a triple-layered coaxial fibre structure was fabricated for strain sensor applications. The core consisted of melt-spun poly (ethylene terephthalate) (PET) where in a subsequent step carbon black (CB) particles were coated onto the surface of the PET fibre to build the conductive pathways by a dissolving-coating method. For the outer protective sheath, a thermoplastic polyurethane (TPU) with a thickness of about 7 μm was generated using a layer-by-layer assembly technique. Compared with other investigated CB-coated fibres, the novel triple hierarchic PET/CB/TPU composite fibres exhibit a high Young's modulus and tensile strength, as well as a doubled sensing range. The fabrication process can be directly used in the textile industry for the production of wearable and flexible sensors due to its efficacy and low cost. Moreover, a model based on tunnelling theory utilizing only two adjustable parameters was modified based on the actual experimental data, which could precisely describe the relative change of resistance upon the applied strain. Meanwhile, an empirical equation was first proposed and this model offers an effective but simple approach towards quantitative analysis of strain sensors.
CRIS-Team Scopus Importer:2019-12-20
Keywords: A. Polymer (textile) fibres; B. Physical properties; C. Analytical modelling; E. Surface treatments